Macroeconomic Changes and Financing of Public Investment Projects - Krzysztof JAROSIŃSKI (Communications of International Proceedings, 2022)
An important and often posed postulate is to create conditions for sustainable development. Striving for the stability of development processes is a challenge that requires the activation of various mechanisms at the state level and regions, as well as on a global basis. An important requirement of sustainable development is ensuring the broadly understood stability of the course of economic processes. However, in the face of crisis phenomena, the general equilibrium and partial equilibria are upset. This has an impact on the implementation of investment projects, including projects in the public sector. The main threats to the implementation of public investment projects may be excessive inflation, the occurrence of an excessive budget deficit, excessive public debt, changes in interest rates, and many other macroeconomic factors. In the conditions of the crisis, there is a real risk of limiting the possibilities of financing investments. The article aims to indicate the negative macroeconomic changes caused by crisis phenomena, which may lead to a deterioration in the conditions of financing public investments. The latest empirical research proves that changes in the conditions of financing investments have already been noted. As a result, it becomes necessary to undertake detailed research and analyses on public investment projects implemented in new socio-economic conditions.
Keywords: public finance; public investments; economy